EXPOSURE TO MASS MEDIA AS A DOMINANT FACTOR INFLUENCING PUBLIC STIGMA TOWARD MENTAL ILLNESS BASED ON SUNRISE MODEL APPROACH - Ni Made Sintha Pratiwi; Lilik Zuhriyah; Lilik Supriati (Belitung Nursing Journal, 2018)
Background: The person suffering mental disorders is not only burdened by his condition but also by the stigma. The impact of stigma extremely influences society which is considered to be an obstacle in the mental disorder therapy. Stigma as the society adverse view towards severe mental disorders is related with the cultural aspect. The interaction appeared from each component of nursing model, called sunrise model, is a model developed by Madeleine Leininger that connects with the wide society views about severe mental disorders condition. Objective: The aim of this study was to analyze the factors related to public stigma and to find out the dominant factors related to public stigma about severe mental illness through sunrise model approach in Indonesia. Methods: This study used observational analytical design with cross sectional approach. There were 150 respondents contributed in this study selected using purposive sampling technique. Spearman Rank and multiple logistic regression were used for data analysis. Results: The results showed a significant relationship between mass media exposure, spiritual well-being, interpersonal contact, attitude, and knowledge with public stigma about mental illness. The result of multiple logistic regression revealed that the low exposure of mass media had the highest OR value at 26.744. Conclusion: There were significant correlations between mass media exposure, spiritual well-being, interpersonal contact, attitude, and knowledge with public stigma toward mental illness. Mass media exposure was a dominant factor influencing public stigma toward mental illness.